Assessment of anxiety, stress and depression in primary dysmenorrhic females - Firdous, Uzma; Noaima Fatima; Yasmeen, Ghazala (International Journal of Endorsing Health Science Research, 2019)
Background: Dysmenorrhea is the most common gynecological complaint, adversely affects the quality life and work productivity in females of reproductive age. Risk factors for primary dysmenorrhea include age, early menarche, low body mass index (BMI), menorrhagia, family history, smoking, nulliparity, depression and stress. This study was carried to find out the pattern of dysmenorrhea in young Pakistani females, and to determine its association with stress, depression and anxiety. Methodology: This was a cross sectional questionnaire based study conducted on 300 female participants of age 20-30 years studying at the local university. Healthy, nulliparous females with the occurrence of dysmenorrhea were included in the study whereas those females who had gynecological, psychological or other medical problems were excluded from the study. Students were asked to provide the information about their socioeconomic status, dysmenorrheal symptoms, mental health status, their habits and other medical characteristics. To evaluate the effect of stress, depression and anxiety, Depression, Anxiety Stress Scale (DASS) was used. All statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) version 16. Results: Of the total dysmenorrhic females 31% were married, 57% had positive family history of dysmenorrhea, 18% of the subjects had BMI<18Kg/m2 while 39% reported high waist hip ratio (WHR). The incidence of menstrual irregularity and menorrhagia was identified in 67% and71%, respectively while passing of clots were found to be in 71% subjects. Significant differences were observed in terms of anxiety (p=0.025) and stress (p=0.028) between the two groups but there was no statistical difference in the levels of depression (p=0.11). It was found that depression is a common complaint irrespective of presence or absence of dysmenorrhea during periods. Conclusion: This study shows that high stress level and anxiety were positively associated with primary dysmenorrhea in young adolescent females. Therefore, mental health promotion and counselling measures should be taken to lessen the severity of dysmenorrhea.